Development and Clinical Application of Positron Emission Tomography Imaging Agents for Monoamine Oxidase B - Meyer, Jeffrey H.; Braga, Joeffre (Frontiers in Neuroscience, 2022)
Monoamine Oxidase B (MAO-B) is a high density protein in brain mainly found on outer mitochondrial membranes, primarily in astroglia, but additionally in serotonergic neurons and in the substantia nigra in midbrain. It is an enzyme that participates in the oxidative metabolism of important monoamines including dopamine, norepinephrine, benzylamine and phenylethylamine. Elevated MAO-B density may be associated with astrogliosis and inhibiting MAO-B may reduce astrogliosis. MAO-B density is elevated in postmortem sampling of pathology for many neuropsychiatric diseases including Alzheimer’s Disease, Parkinson’s Disease, Huntington’s Disease, Amyotrophic Lateral Sclerosis and alcohol use disorder. Initial positron emission tomography (PET) radiotracer development focused on analogues of [11C]deprenyl, with the most commonly applied being the deuterium substituted [11C]deprenyl-D2. This latter radiotracer was modelled with an irreversible trapping compartment reflecting its irreversible binding to MAO-B. Subsequently, [11C]SL2511.88, a reversible binding MAO-B radiotracer with outstanding properties including high specific binding and excellent reversibility was developed. [11C]SL25.1188 PET was applied to discover a substantive elevation of MAO-B binding in the prefrontal cortex in major depressive disorder (MDD) with an effect size of more than 1.5. Longer duration of MDD was associated with greater MAO-B binding throughout most grey matter regions in brain, suggesting progressive astrogliosis. Important applications of [11C]deprenyl-D2 PET are detecting a 40% loss in radiotracer accumulation in cigarette smokers, and substantial occupancy of novel therapeutics like EVT301 and sembragiline. Given the number of diseases with elevations of MAO-B density and astrogliosis, and the advance of [11C]SL25.1188, clinical applications of MAO-B imaging are still at an early stage.